2020
DOI: 10.1017/aer.2019.162
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of current rotor design comparison practices based on high-fidelity CFD methods

Abstract: This paper provides an assessment of current rotor design comparison practices. First, the employed CFD method is validated for a number of rotor designs and is shown to achieve accurate performance predictions in hover and high-speed forward flight. Based on CFD results, a detailed investigation is performed in terms of comparing different rotor designs. The CFD analysis highlighted the need of high fidelity methods due to the subtle aerodynamics involved in advanced planforms. Nevertheless, the paper suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Specifically for wind turbine applications, significant progress has been made by the National Renewable Energy Laboratory (NREL) in streamlining the progress of completing large-eddy simulation (LES) atmospheric boundary layer simulations coupled with wind turbines through their OpenFAST tool sets (Jonkman, 2013). Through leveraging such tool sets, studies of isolated rotors have been shown to be capable of resolving flow fields relevant for performance and loads of isolated rotors in hover/forward flight (Fitzgibbon et al, 2020), during rotorcraft pitch-up maneuvers (Abhishek et al, 2011), and in rotorship wake interactions (Crozon et al, 2018). Many recent publications have demonstrated the feasibility of deploying such modeling techniques for wind turbine applications.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically for wind turbine applications, significant progress has been made by the National Renewable Energy Laboratory (NREL) in streamlining the progress of completing large-eddy simulation (LES) atmospheric boundary layer simulations coupled with wind turbines through their OpenFAST tool sets (Jonkman, 2013). Through leveraging such tool sets, studies of isolated rotors have been shown to be capable of resolving flow fields relevant for performance and loads of isolated rotors in hover/forward flight (Fitzgibbon et al, 2020), during rotorcraft pitch-up maneuvers (Abhishek et al, 2011), and in rotorship wake interactions (Crozon et al, 2018). Many recent publications have demonstrated the feasibility of deploying such modeling techniques for wind turbine applications.…”
Section: Introductionmentioning
confidence: 99%
“…have been developed to help streamline the process of CFD simulation of rotors. Large Eddy Simulation (LES) (Smagorinsky, 1963) and Detached Eddy Simulations (DES) (Spalart, 1997) studies of isolated rotors have shown to be capable of resolving flow fields relevant for performance and loads of isolated rotors in hover/forward flight (Fitzgibbon et al, 2020), during rotorcraft pitch up maneuvers (Abhishek et al, 2011), and rotor-ship wake interactions (Crozon et al, 2018). In a recent publication by Sood et al (2022), high-fidelity LES simulations were completed for five different inflow conditions of the Lillgrund wind farm.…”
Section: Introductionmentioning
confidence: 99%